Learning Innovation Content Creators Social Media-Based Qualitative Analysis to Improve Motivation and Learning Outcomes of Professional Teacher Candidates: A Systematic Literature Review - Widarti, Hayuni Retno; Anggraini, Tria; Rokhim, Deni Ainur; Syafruddin, Afis Baghiz (Orbital: The Electronic Journal of Chemistry, 2022)
Students need motivation in order to increase their interest and focus of students. One way to increase students’ learning motivation is by presenting interesting learning media for students. Social media is an audio-visual platform that steals the attention of many people in various groups, especially children to teenagers. The method applied in this research is the systematic literature review (SLR) method. The SLR method is used to identify, review, evaluate and interpret all available studies in a subject area of interest to a phenomenon involving a particular related research question. In the Literature Review Study that has been described, it can be concluded that research on Creator Content in Social Media-Based Chemistry Learning Media can be carried out with various considerations of research results similar to the Multi-representation approach which can increase student motivation and learning outcomes.